Activity-Based Protein Profiling Reveals That Cephalosporins Selectively Active on Non-replicating Mycobacterium tuberculosis Bind Multiple Protein Families and Spare Peptidoglycan Transpeptidases - Lopez Quezada, Landys; Smith, Robert; Lupoli, Tania J.; Edoo, Zainab; Li, Xiaojun; Gold, Ben; Roberts, Julia; Ling, Yan; Park, Sae Woong; Nguyen, Quyen; Schoenen, Frank J.; Li, Kelin; et al. (Frontiers in Microbiology, 2020)
As -lactams are reconsidered for the treatment of tuberculosis (TB), their targets are assumed to be peptidoglycan transpeptidases, as verified by adduct formation and kinetic inhibition of Mycobacterium tuberculosis (Mtb) transpeptidases by carbapenems active against replicating Mtb. Here we investigated the targets of recently described cephalosporins that are selectively active against nonreplicating (NR) Mtb. NR-active cephalosporins failed to inhibit recombinant Mtb transpeptidases. Accordingly, we used alkyne analogs of NR-active cephalosporins to pull down potential targets through unbiased activity-based protein profiling and identified over 30 protein binders. None was a transpeptidase. Several of the target candidates are plausibly related to Mtb’s survival in an NR state. However, biochemical tests and studies of loss of function mutants did not identify a unique target that accounts for the bactericidal activity of these beta-lactams against NR Mtb. Instead, NR-active cephalosporins appear to kill Mtb by collective action on multiple targets. These results highlight the ability of these -lactams to target diverse classes of proteins.